Larvicidal Effect of Breadfruit (Artocarpus altilis) Flower Extract Against Aedes aegypti - Winianti, Ni Wayan; Budi Apsari, Putu Indah; Jayanti, Ni Kadek Meta (Folia Medica Indonesiana, 2024)
Highlights: 1. This study attempted an experiment on the novel invention of a naturally sourced larvacide, specifically breadfruit (Artocarpus atilis) flower extract, against Aedes aegepti. 2. The findings of this study suggest that breadfruit flower extract can serve as an effective larvacide, as evident by an increased mortality rate of Aedes aegepti larvae. Abstract Dengue hemorrhagic fever remains a major problem in Indonesia. The mosquito that spreads this disease is the Aedes aegypti species. The use of larvicides is a viable method to inhibit the growth of larvae into adult mosquitoes. The flowers of breadfruits (Artocarpus atilis) have long been used as a natural mosquito killer. The objectives of this study were to determine the lethal dose 50 (LC50) of breadfruit flower extract and to analyze its potential as a larvicide against stage 2–3 instar Aedes aegypti larvae. In this true experimental research, each of four treatment groups was administered with breadfruit flower extracts at concentrations of 25, 50, 75, and 90 ppm, respectively. The positive control group was treated with temephos (Abate), while the negative control group received no treatment. Larval mortality was recorded at 1 hour, 2 hours, 3 hours, 4 hours post-intervention. The observed larval deaths were compared among the groups. Quantitative data encompassing the larval mortality in each group were analyzed using the repetitive analysis of variance (ANOVA) and the probit test with minimum p value <0.05. The results indicated that the LC50 value of breadfruit flower extract was 52.67–54.12 ppm. The doses of 50 ppm, 75 ppm and 90 ppm were effective in killing Aedes aegypti larvae. In conclusion, breadfruit flower extract of 50 ppm and higher can effectively kill Aedes aegypti larvae.